Dynamic surface control-backstepping based impedance control for 5-DOF flexible joint robots - Xiong, Gen-liang; Xie, Zong-wu; Huang, Jian-bin; Liu, Hong; Jiang, Zai-nan; Sun, Kui (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2010)
A new impedance controller based on the dynamic surface control-backstepping technique to actualize the anticipant dynamic relationship between the motion of end-effector and the external torques was presented. Comparing with the traditional backstepping method that has “explosion of terms” problem, the new proposed control system is a combination of the dynamic surface control technique and the backstepping. The dynamic surface control (DSC) technique can resolve the “explosion of terms” problem that is caused by differential coefficient calculation in the model, and the problem can bring a complexity that will cause the backstepping method hardly to be applied to the practical application, especially to the multi-joint robot. Finally, the validity of the method was proved in the laboratory environment that was set up on the 5-DOF (degree of freedom) flexible joint robot. Tracking errors of DSC-backstepping impedance control that were 2.0 and 1.5 mm are better than those of backstepping impedance control which were 3.5 and 2.5 mm in directions X , Y in free space, respectively. And the anticipant Cartesian impedance behavior and compliant behavior were achieved successfully as depicted theoretically.